Hubungan Tingkat Perekonomian, Pekerjaan Orangtua dan Letak Geografis dengan Minat Belajar Pendidikan Jasmani Olahraga dan Kesehatan di Masa Pandemi Covid-19 di SMA Widiatmika Jimbaran Badung - Dewi Dendy Pratiwi; I Ketut Yoda; Made Agus Dharmadi (Journal on Education, 2023)
This study aims to determine the significant relationship between economic level, parental occupation and geographic location with interest in learning physical education, sports and health during the COVID-19 pandemic at Widiatmika High School. The research method used is correlation. The subjects of this study were all students at SMA Widiatmika. The data analysis technique used is the Pearson product moment technique and multiple linear regression analysis. The results of this study indicate: 1) There is a positive and significant relationship between the level of the economy and interest in learning physical education, sports and health during the COVID-19 pandemic. 2) There is a positive and significant relationship between work and interest in learning physical education, sports and health during the covid-19 pandemic. 3) There is a positive and significant relationship between geographic location and interest in learning physical education, sports and health during the COVID-19 pandemic. 4) There is a positive and significant relationship between the level of economy, occupation and geographical location with interest in learning physical education, sports and health during the covid-19 pandemic.